2011
DOI: 10.1002/joc.2340
|View full text |Cite
|
Sign up to set email alerts
|

How do Himalayan areas respond to global warming?

Abstract: ABSTRACT:We study the interdecadal-scale variability over the Himalayas/Tibetan Plateau (H/TP) to deepen the understanding of Earth's important ecosystem after the recent controversy about glaciers melting in the Himalayan Mountains. We present a new statistical reconstruction of annual temperature variability back to 1901 for the Pyramid Automated Weather Station of the Ev-K2-CNR Committee, located at the base of the Mount Everest. Our reconstruction using recorded weather station data compared with the Clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The transition between the monsoon and post-monsoon seasons, passing from cloudy, rainy and warm to clear, dry and cold, takes no more than a few days. Consequently, changes in future monsoon onset, duration and intensity (Turner & Annamalai, 2012) will have significant impacts on glacier melt and accumulation processes (Diodato, Bellocchi, & Tartari, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition between the monsoon and post-monsoon seasons, passing from cloudy, rainy and warm to clear, dry and cold, takes no more than a few days. Consequently, changes in future monsoon onset, duration and intensity (Turner & Annamalai, 2012) will have significant impacts on glacier melt and accumulation processes (Diodato, Bellocchi, & Tartari, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A summary of selected high-elevation automatic weather stations (AWS) in the HKH region, with elevation (Z) and on-or off-glacier designation, station type (A ¼ year-round, S ¼ seasonal/temporary), and type of observations: T ¼ temperature, RH ¼ relative humidity, P ¼ precipitation, u ¼ wind speed, u ¼ wind direction, K # ¼ downwelling short-wave radiation, L # ¼ downwelling long-wave radiation, p ¼ atmospheric pressure. Sources: Ageta, Ohata, Tanaka, Ikegami, and Higuchi (1980); Bollasina, Bertolani, and Tartari (2002); Diodato et al (2012);Higuchi (1977); Higuchi, Ageta, Yasunari, and Inoue (1982); Mihalcea et al (2006); Mölg et al (2012); Moore and Semple (2004);Takeuchi (2000); Wagnon et al (2013);Yang, He, Tang, Qin, and Cheng (2010); Zhang et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 1.6 °C warming in the last century is reported over north-western Himalayan region by Bhutiyani et al (2007). In a recent study based on Climatic Research Unit's reconstructed temperature dataset it was found that the Himalayas and Tibet Plateau have warmed at a higher rate in the last few decades than that in the last century (Diodato et al 2012). Dash et al (2007) reported that western Himalayas warmed by over 0.9 °C during 1901-2003. Season specific responses to warming is also reported over the Himalayans.…”
Section: Introductionmentioning
confidence: 93%
“…IPCC 2013 ). At higher elevations, temperature has been increasing at a rate of up to 1.2 °C per decade since about 1980 (Shrestha et al 1999 ;Liu et al 2006Liu et al , 2009Bhutiyani et al 2007Bhutiyani et al , 2010Shrestha and Aryal 2011 ;Yang et al 2011 ), with an accelerating warming trend in the past two decades (Diodato et al 2011 ;Kattel and Yao 2013 ;Gerlitz et al 2014 ;Hasson et al 2015 ).…”
Section: Climate Changementioning
confidence: 97%